2022
DOI: 10.1177/00048674221106669
|View full text |Cite
|
Sign up to set email alerts
|

Clinical correlates of comorbid attention deficit hyperactivity disorder in adults suffering from bipolar disorder: A meta-analysis

Abstract: Objective: Attention deficit hyperactivity disorder is a frequent comorbid condition in adults with bipolar disorder. We performed a meta-analysis aimed at assessing sociodemographic and clinical correlates of attention deficit hyperactivity disorder in bipolar disorder. Method: We searched main electronic databases up to June 2021. Random-effects meta-analyses, with relevant meta-regression and quality-based sensitivity analyses, were carried out to estimate the association between attention deficit hyperacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 92 publications
2
11
0
2
Order By: Relevance
“…However, there is accumulating evidence that other neurodevelopmental vulnerabilities, for example, attention-deficit/hyperactivity disorder (ADHD) symptoms and specific learning disabilities may also serve as prerequisites of trajectories leading to suicide. Indeed, recent meta-analyses found that a diagnosis of ADHD is associated with increased risk of suicidal ideation, plans and attempts as well as completed suicide [ 38 , 39 ]. Also, it has been found that specific learning disorders, including reading disabilities (RDs), are associated with higher risk of suicidal attempts after adjustment for known risk factors, for example, CT, a history of mental disorders and substance abuse [ 40 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, there is accumulating evidence that other neurodevelopmental vulnerabilities, for example, attention-deficit/hyperactivity disorder (ADHD) symptoms and specific learning disabilities may also serve as prerequisites of trajectories leading to suicide. Indeed, recent meta-analyses found that a diagnosis of ADHD is associated with increased risk of suicidal ideation, plans and attempts as well as completed suicide [ 38 , 39 ]. Also, it has been found that specific learning disorders, including reading disabilities (RDs), are associated with higher risk of suicidal attempts after adjustment for known risk factors, for example, CT, a history of mental disorders and substance abuse [ 40 ].…”
Section: Introductionmentioning
confidence: 99%
“…It can be hypothesized that other psychological and/or medical conditions for which patients report AD or HI may also make these patients more vulnerable for having accidents and injury. Several psychological and medical conditions have ADHD as comorbidity, including mood disorders (e.g., anxiety, depression), substance use disorders, personality disorders, autism, and insomnia [ 17 ]. In addition, neurological and digestive diseases have been associated with ADHD symptomatology as well [ 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Following a similar approach used in recent meta-analyses, 27 , 28 we used GRADE (Grading of Recommendations, Assessment, Development, and Evaluations) items, 29 adapted for non-interventional observational studies, to classify the quality of evidence as high, moderate, low or very low for each variable showing a statistically significant estimate ( P < 0.05).…”
Section: Methodsmentioning
confidence: 99%